Identifikasi lahan pertanian pangan berkelanjutan (LP2B) pada lahan sawah di Kampung bowi subur (SP 6) Distrik masni - Muller Manuel Arisoy; Samsul Bachri; Siti Hadjar Kubangun; Alce Ilona Noya (Fakultas Pertanian Universitas Papua, 2021)
The purpose of this study was to identify the area distribution of Sustainable Food Agricultural Land (LP2B) in Bowi Subur Village (SP6) Masni District. The methods used are spatial methods and field surveys. Observational variables in this study include data on paddy fields based on lowland rice cultivation techniques, lowland rice productivity results, irrigation facilities and farmer responses regarding lowland rice cultivation. The results of this study found that Bowi Subur Village in recent years experienced a decrease in productivity, which was only 0.69 to 1.1 tons/ha due to the acidic nature of the soil, and damaged irrigation networks that were still being renovated, so to meet the needs of life, farmers sold land. rice fields, and finally change the function of the land. There were 3 categories of land availability for LP2B in Bowi Subur Village, namely very eligible, eligible and inappropriate. Very eligible criteria for LP2B has an area of ​​14 ha, while Eligible criteria and unfeasible criteria for LP2B have area of ​​23.5 ha and ​​11 ha, respectively.